The Effectiveness of Discovery Learning Method on Reading Descriptive Text at Eighth Grade of SMP Diniyah Al Falahiyah Lamongan - Muhammad Luthfi Abdillah (Journal of Education and Religious Studies, 2021)
This researcher measures the effectiveness of discovery learning on reading descriptive text at eight grades of SMP Diniyah Al Falahiyah Lamongan in academic 2020/202. The discovery learning method strategy works for the students' mental, easy to interact (actively) and new information independently. The method of the research utilized a quantitative experimental method by using a pre-experimental design. Conducted the sample of the study was at VII-A class with 30 students. The instrument of collecting data used try-out and test (pre-test and post-test). The test had utilized to know students' abilities before and after the experiment run. The result of the research showed the mean score in the pre-test was 57.33, and the post-test was 74.50. The result was that the post-test was higher than the pre-test. The analysis using the SPSS based paired sample t-test formula produces a significance value of sig. (2-tailed) had 0.000 at the critical value for the 5% level (0.000 < 0.05). The obtained t-test had -21.908, and the t-table was 2.042. So, the test score was higher than the t-table (-21.908 > 2.042). It means rejected Ho and Ha is accepted. It can conclude that the discovery learning method has significant and effectiveness to reading descriptive text.